LeviSense: A platform for the multisensory integration in levitating food and insights into its effect on flavour perception. Issue 139 (July 2020) - Vi, Chi Thanh; Marzo, Asier; Memoli, Gianluca; Maggioni, Emanuela; Ablart, Damien; Yeomans, Martin; Obrist, Marianna
Highlights: LeviSense is the first system integrating all five senses with levitated food. Technical and perceptual challenges in the design of each sensory input unit. Different lighting and smell conditions affect the perceived taste perception. LeviSense creates a new design space, and enables novel taste-based interactions. Abstract: Eating is one of the most multisensory experiences in everyday life. All of our five senses (i.e. taste, smell, vision, hearing and touch) are involved, even if we are not aware of it. However, while multisensory integration has been well studied in psychology, there is not a single platform for testing systematically the effects of different stimuli. This lack of platform results in unresolved design challenges for the design of taste-based immersive experiences. Here, we present LeviSense: the first system designed for multisensory integration in gustatory experiences based on levitated food. Our system enables the systematic exploration of different sensory effects on eating experiences. It also opens up new opportunities for other professionals (e.g., molecular gastronomy chefs) looking for innovative taste-delivery platforms. We describe the design process behind LeviSense and conduct two experiments to test a subset of the crossmodal combinations (i.e., taste and vision, taste and smell). Our results show how different lighting and smell conditions affect the perceived taste intensity, pleasantness, and satisfaction. We discuss how LeviSense creates a new technical, creative, and expressive possibilities in a series of emerging design spaces within Human-Food Interaction.